Vivencias de madres de niños con sindrome de down - Torres García, Grecia Paola (2011)
This phenomenological qualitative study, had been performed in mothers whose children have Down syndrome who go to the Special Education Center "Carlos A. Mannucci " in order to comprehend the experiences of mothers in the day to day with their children, shows the phenomenon of these emotions lived through highlighting categories: sadness, rejection, acceptance, living together, skills development of Down Syndrome’s children Participated in this investigation two mothers of children who are six years old, which they were interviewed by our guiding question: "Tell me in detail everything he does and lives every day with their son? “ The speeches and their meanings have been analyzed in light of Heideggerian phenomenology in the new mode of being of presence. The comprehension of this phenomenon is important to the experiences of mothers with children with Down syndrome to achieve integral action in her "way-of-being", her decision before the birth of a child with special skills and his new "being-in-the-world" as the mother of a special child, likewise ensuring the development and integration of children with Down syndrome in society as an alternative to health promotion.